Smart Contract Security Auditing Frameworks: Towards Reliable Decentralized Applications (Blockchain, Web3 & Digital Trust Journal p-ISSN 3117-597X and e-ISSN 3117-5988, 2025)
Smart contracts lie at the heart of decentralized applications (DApps) in blockchain ecosystems, automating transactions without intermediaries. However, vulnerabilities in smart contract code have led to multimillion-dollar losses, undermining trust in decentralized finance (DeFi) and Web3 platforms. This paper explores existing smart contract security auditing frameworks, their methodologies, and how they contribute to building reliable and tamper-proof decentralized applications. By comparing leading auditing tools and frameworks—including Mythril, Slither, Oyente, and Certora Prover—across Ethereum and other EVM-compatible blockchains, the study proposes an integrated auditing framework combining static and dynamic analysis, formal verification, and continuous monitoring. The findings suggest that hybrid auditing approaches enhance reliability, reduce gas inefficiencies, and significantly minimize exploit risks, thereby advancing the security foundations of decentralized ecosystems.